Lycopene Prevents Development of Steatohepatitis in Experimental Nonalcoholic Steatohepatitis Model Induced by High-Fat Diet - Ibrahim Halil Bahcecioglu; Nalan Kuzu; Kerem Metin; Ibrahim Hanifi Ozercan; Bilal Ustündag; Kazim Sahin; Omer Kucuk (Veterinary Medicine International)
We investigated the preventive effect of lycopene on nonalcoholic steatohepatitis-induced by high-fat diet in rats. Forty male Sprague-Dawley rats were divided into 4 groups. They were fed standard diet, high-fat diet (HFD), high-fat diet plus lycopene at a dose of 2 mg/kg body weight and the high-fat diet lycopene at a dose of 4 mg/kg BW for a period of 6 weeks. Inflammation, steatosis, 𝛼-smooth muscle actin (𝛼-SMA), and cytochrome P450 2E1 (CYP 2E1) expression increased significantly in the rats fed HFD and decreased in the rats administered by lycopene. Significantly elevated levels of serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), tumor necrosis factor (TNF 𝛼), and serum and liver malondialdehyde (MDA) were observed in rats fed the high-fat diet as compared to the control rats (𝑃<.01). Supplementation with lycopene lowered serum MDA and tumor necrosis factor (TNF-𝛼) levels and elevated liver GSH level (𝑃<.001). Insulin resistance was higher in the rats fed HFD than in rats supplemented with lycopene. The data indicate that supplementation with lycopene can reduce high-fat diet-induced oxidative stress to the cells.